2013
DOI: 10.1002/qua.24585
|View full text |Cite
|
Sign up to set email alerts
|

Shape and location of multiple charge carriers in linear π-electron systems

Abstract: We have performed a quantum-mechanical study of a series of neutral polyenes, their multiply charged ions, and related ionic polymethines with a closed electron shell, using different methods/basis with/without electron correlations. The study shows that a multiple injection of charge carriers into a collective system of p-electrons causes a formation of distinctive electron levels in the energy gap along with a simultaneous regular gap shift in accordance to the number of injected carriers. Each charge genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…According to this view, the charge in the collective π-system is neither localized in only one atom (π-center) nor uniformly delocalized along the conjugated system, but produces a solitonic wave of partial charges, so that the charges at neighboring carbon atoms alternate considerably [146][147][148][149]. Besides, it was established and quantum-chemically examined that the multiple injection of the k charges causes an appearance of the k solitons [151,153].…”
Section: Symmetry Breakingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this view, the charge in the collective π-system is neither localized in only one atom (π-center) nor uniformly delocalized along the conjugated system, but produces a solitonic wave of partial charges, so that the charges at neighboring carbon atoms alternate considerably [146][147][148][149]. Besides, it was established and quantum-chemically examined that the multiple injection of the k charges causes an appearance of the k solitons [151,153].…”
Section: Symmetry Breakingmentioning
confidence: 99%
“…J.-L.Bredas [152] in his work concerning the theoretical study of the electron structure of the ions of the conjugated polymers has shown M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 23 that the occurrence of charge in the π-system leads to an appearance of the specific electron level: so-called soliton level or charge level. Later [146,153,154], it was found that going from the neutral π-system to its cation or anion causes a substantial shift of the energy gap down-or upwards, correspondingly.…”
Section: Introduction Of π π π π-Donor Substituents To Terminal Groupsmentioning
confidence: 98%
See 1 more Smart Citation
“…The injection of the charge in the collective π‐system is known to cause the alternation of the partial positive and negative charges at the neighboring carbon atoms. And, the total charge +1 exist in the whole molecule, and hence this deficit of the electron density should polarize more strong the σ‐bonds between the hydrogen and carbon atom.…”
Section: Resultsmentioning
confidence: 99%
“…The injection of multiple charges should generate the corresponding number of the solitons . Detail study of features of the two positively charged linear conjugated systems was performed in the previous paper; it was shown that ionization by two electrons results in formation of two solitonic waves of charge alternation, rather than superposition of two overlapping solitonic waves.…”
Section: Introductionmentioning
confidence: 99%